Effectiveness of Curcuma longa L on the growth Inhibition of Streptococcus sanguinis - Dohude, Gostry Aldica; Rusdy, Hendry; Hanafiah, Olivia Avriyanti; Br Ginting, Rachel Adinda Yule (Journal of Syiah Kuala Dentistry Society, 2023)
Background: A dry socket is a severe pain one to three days after tooth extraction. Streptococcus sanguinis (S. sanguinis) is reported to inhibit the healing process of dry sockets. Curcuma longa L contains flavonoids, tannins, saponins, and alkaloids which have the potential as antibacterials. Objective. This study evaluated the antibacterial properties of Curcuma longa L. on the S. sanguinis. Materials and Methods: This experimental study used a post-test-only control group design. Turmeric leaf extract is made by using the maceration extraction method. The method used in the inhibition test used Kirby-Bauer disc diffusion with five samples for each treatment. The sample consisted of five treatment groups: turmeric leaf extract with concentrations of 10%, 15%, and 20%, and positive control (clindamycin) and negative control (DMSO) groups. Data were analyzed using the One Way ANOVA and Post Hoc tests. Results. The results of data analysis using ANOVA showed a p-value of 0.00 on inhibition, which means that turmeric leaf extract can inhibit the growth of S. sanguinis. The average inhibition zone obtained was 9.52 mm at a concentration of 10%, at a concentration of 15% at 9.84 mm, and at a concentration of 20% at 10.18 mm. Conclusion: Curcuma longa L extract inhibited the growth of S sanguinis on a moderate scale. Higher concentrations showed the best inhibition values.